Community, trophic structure and functioning in two contrasting Laminaria hyperborea forests. (5th January 2015) - Leclerc, Jean-Charles; Riera, Pascal; Laurans, Martial; Leroux, Cédric; Lévêque, Laurent; Davoult, Dominique
Abstract: Worldwide kelp forests have been the focus of several studies concerning ecosystem dysfunction in the past decades. Multifactorial kelp threats have been described and include deforestation due to human impact, cascading effects and climate change. Here, we compared community and trophic structure in two contrasting kelp forests off the coasts of Brittany. One has been harvested five years before sampling and shelters abundant omnivorous predators, almost absent from the other, which has been treated as preserved from kelp harvest. δ 15 N analyses conducted on the overall communities were linked to the tropho-functional structure of different strata featuring these forests (stipe and holdfast of canopy kelp and rock). Our results yielded site-to-site differences of community and tropho-functional structures across kelp strata, particularly contrasting in terms of biomass on the understorey. Similarly, isotope analyses inferred the top trophic position of Marthasterias glacialis and Echinus esculentus which may be considered as strong interactors in the sub-canopy. We interrogate these patterns and propose a series of probable and testable alternative hypotheses to explain them. For instance, we propose that differences of trophic structure and functioning result from confounded effects of contrasting wave dissipation depending on kelp size-density structure and community cascading involving these omnivorous predators. Given the species diversity and complexity of food web highlighted in these habitats, we call for further comprehensive research about the overall strata and tropho-functional groups for conservation management in kelp forests.